2014
DOI: 10.1590/01047760201420031425
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento inicial de Stryphnodendron polyphylum (Mart.) em resposta à adubação com N e P

Abstract: CRESCIMENTO INICIAL DE Stryphnodendron polyphylum (Mart.) EM RESPOSTA À ADUBAÇÃO COM N E P RESUMO: O barbatimão é uma importante espécie nativa do Cerrado, com potencial econômico e de restauração de áreas degradadas, no entanto, são escassos estudos agronômicos com a espécie, principalmente no que se refere à adubação com nitrogênio e fósforo em solos de Cerrado. Assim, objetivou-se estudar o crescimento inicial e índice SPAD em função de doses de N e P em Latossolo Vermelho distroférrico. O trabalho foi dese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(12 reference statements)
0
3
1
3
Order By: Relevance
“…Pata-de-vaca seedlings (Bauhinia forficata Link), a pioneer species naturally occurring throughout Brazil, presented higher shoot dry mass when concentrations of 200 mg dm -3 P 2 O 5 and 75 mg dm -3 N were applied ( RAMOS et al, 2000). The maximum shoot dry mass value (7.14 g) in the initial growth of Stryphnodendron polyphylum (barbatimão) was found at concentrations of 62.46 mg kg -1 N and 125.16 mg kg -1 P 2 O 5 (SOUZA et al, 2014), concentrations below those found in this work for the production of barueiro seedlings, indicating the importance of the association between nutrients (N and P) to provide greater growth of native species seedlings. Figure 4 shows that when nitrogen was applied, the fresh root mass of barueiro seedlings showed linear growth, with increment of 0.005 g of fresh root mass for each mg P 2 O 5 added to the soil.…”
Section: Resultscontrasting
confidence: 72%
“…Pata-de-vaca seedlings (Bauhinia forficata Link), a pioneer species naturally occurring throughout Brazil, presented higher shoot dry mass when concentrations of 200 mg dm -3 P 2 O 5 and 75 mg dm -3 N were applied ( RAMOS et al, 2000). The maximum shoot dry mass value (7.14 g) in the initial growth of Stryphnodendron polyphylum (barbatimão) was found at concentrations of 62.46 mg kg -1 N and 125.16 mg kg -1 P 2 O 5 (SOUZA et al, 2014), concentrations below those found in this work for the production of barueiro seedlings, indicating the importance of the association between nutrients (N and P) to provide greater growth of native species seedlings. Figure 4 shows that when nitrogen was applied, the fresh root mass of barueiro seedlings showed linear growth, with increment of 0.005 g of fresh root mass for each mg P 2 O 5 added to the soil.…”
Section: Resultscontrasting
confidence: 72%
“…O teor de P foi maior nos tratamentos adubação + calagem, seguido de adubação + calagem + hidrogel e adubação + hidrogel, não sendo observada diferença significativa entre eles. Devido ao fósforo ser um nutriente fortemente adsorvido aos óxidos de ferro e alumínio (Souza et al, 2014), a utilização da calagem pode ser muito benéfica, pois além de elevar os teores de Ca e Mg e reduzir os teores solúveis de Fe e Al do solo, também aumenta a concentração de P lábil na solução do solo, tornando-o disponível para as plantas (Silva et al, 2007). Hidrogel, calagem e As menores concentrações de P nos tratamentos controle e hidrogel são justificáveis pela ausência de adubação e calagem, mantendo-se baixa a concentração deste elemento no solo.…”
Section: Resultsunclassified
“…Os solos brasileiros são, em sua maioria, antigos e altamente intemperizados, ácidos e com baixa disponibilidade de nutrientes, especialmente os do Cerrado, o que torna necessária a correção e adubação para níveis adequados ao desenvolvimento das plantas (Souza et al, 2014). Nesse ecossistema, o desenvolvimento das raízes é abreviado pelo excesso de alumínio trocável e também pela deficiência de cálcio, limitando a absorção de água e nutrientes e, consequentemente, a redução da produtividade da madeira do eucalipto (Costa et al, 2014).…”
Section: Introductionunclassified
“…According to Soares et al (2013), H. stigonocarpa is a typical species of acid soils and is not very demanding for nutrients to develop. Even considering that native Cerrado plants are adapted to low fertility soils, experimental fertilization studies indicate that woody species may respond to soil fertilization, especially when these nutrients are nitrogen and phosphorus (Scholz et al, 2007), since these are the most limiting nutrients for plant growth and development (Souza et al, 2014), acting in several important processes for the survival and growth of plants. For example, phosphorus acts in most metabolic processes of enzymes and participates in cell division, photosynthesis, and respiration (Shabnam & Iqbal, 2016).…”
Section: Introduction and Objectivesmentioning
confidence: 99%